Narrative, memory and practice: Tensions and choices in the use of a digital artefact - Lindley, Siân; Randall, Dave; Sharrock, Wes; Glancy, Maxine; Smyth, Nicola; Harper, Richard (Proceedings of the 23rd BCS conference on Human Computer Interaction, 2009)
This paper reports on research into the use of SenseCam, a wearable automatic camera. Household members were given multiple SenseCams to enable an exploration of how the device would be used in the context of everyday life. We argue that understanding the ‘small stories’ created by household members based around SenseCam images requires us to pay attention to a complex amalgam of issues. These pertain to narrative, memory and practice in and through both the ‘sites of expression’ of such work – the topics that are selected for recall – and performativity – the occasions upon which narratives are constructed and the elaborations of identity that are entailed. Finally, we consider how the varied uses of SenseCam that emerged have implications for technologies relating to lifelogging and user-generated content.